2016
DOI: 10.34105/j.kmel.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The use of MOOCs to support personalized learning: An application in the technology entrepreneurship field

Abstract: Massive open online courses (MOOCs) are changing the way in which people can access digital knowledge, thus creating new opportunities for learning and competence development. MOOCs leverage the free and open use of digitized material through supportive on-line systems. MOOCs have gained worldwide popularity and many education providers have started to offer courses in different domains such as innovation management and entrepreneurship tackling recent demands for better employability and social inclusion. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Al-Atabi et al [18] found that as a large-scale open online course, MOOC was a suitable entrepreneurship education platform, which could improve individual's emotions on key aspects of entrepreneurship. Cirulli et al [19] showed that MOOCs could support personalized learning and cultivate college students' ability in the field of technology entrepreneurship. From the existing research literature, the BOPPPS teaching model emphasized the leading role of bridge-in, object, teacher-student communication, participatory learning, testing, and summary for students while retaining the original teaching process.…”
Section: Hypothesismentioning
confidence: 99%
“…Al-Atabi et al [18] found that as a large-scale open online course, MOOC was a suitable entrepreneurship education platform, which could improve individual's emotions on key aspects of entrepreneurship. Cirulli et al [19] showed that MOOCs could support personalized learning and cultivate college students' ability in the field of technology entrepreneurship. From the existing research literature, the BOPPPS teaching model emphasized the leading role of bridge-in, object, teacher-student communication, participatory learning, testing, and summary for students while retaining the original teaching process.…”
Section: Hypothesismentioning
confidence: 99%
“…In the context of mass innovation and entrepreneurship (I&E) in China, the country has vigorously promoted I&E education for college students and listed it as a key education plan for colleges and universities in China. At present, higher educational schools have actively carried out related educational reform programs and taken them as the primary task of their teaching management works [1][2][3][4]. Contemporary college students are the main force of I&E in Chinese society, and a comprehensive evaluation system of college students' I&E thinking ability will play a positive guiding and encouraging role in their I&E activities [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…обсуждаются моделиих развития, механизмы поддержки и методологические аспекты оценки результативности (см., напр. : [Martín-Rojas, Garcia-Morales, Bolivar-Ramos, 2013;Cirulli et al, 2016;Souzaetal., 2018;Tomy, Pardede, 2018]) 9 .Экосистема технологического предпринимательства рассматривается как совокупность финансового капитала, квалифицированных кадров, сетей, законодательства, культуры, инфраструктуры информационных и коммуникационных технологий, рыночного потенциала 10 .…”
unclassified